The age of turbulence adventures in a new world - Greenspan, Alan, 1926- (Penguin Books, 2008)
"'The Age of Turbulence' is Alan Greenspan's incomparable reckoning with the contemporary financial world, channeled through his own experiences working in the command room of the global economy longer and with greater effect than any other single living figure. Following the arc of his remarkable life's journey through his more than eighteen-year tenure as chairman of the Federal Reserve Board to the present, in the second half of 'The Age of Turbulence' Dr. Greenspan embarks on a magnificent tour d'horizon of the global economy."